Analisis Kelayakan Finansial Usaha Peternakan Sapi Perah Di Kabupaten Boyolali Dengan Pendekatan Kuantitatif - Noviyanti, Diva; Aris Eddy Sarwono; Yannie Asrie Widanti (Politeknik Negeri Ambon, 2025)
This research aims to analyze the financial feasibility of dairy farming MSMEs in Boyolali Regency. The research objects used are MSME1 and MSME2. MSME1 is a dairy farming business as well as processing processed animal feed products in Kebonarum Village, Boyolali. MSME2 is a dairy and beef cattle farming business in Lawang Village, Boyolali. Data collection techniques use observation and interview methods. The data analysis used is a quantitative method using Net Present Value (NPV), Gross B/C, Net B/C, Internal Rate Return (IRR) and Pay Back Period (PBP). The novelty of this research is that the analysis not only covers the primary dairy farming business, but also its derivative businesses, thereby providing a more comprehensive picture of the business's financial potential. The research results show that the NPV for MSME1 is IDR. 234,285,762.20 and MSME2 amounting to Rp. 677,396,862.08. The Gross B/C value for MSME1 is 1.08 and MSME2 is 1.12. The Net B/C value for MSME1 is 2.245 and MSME2 is 2.247. The IRR value for MSME1 is 28.65% and MSME2 is 33.17%. PBP for MSME1 for 3 years 4 months and MSME2 for 2 years 7 months. Based on the results of this research, it can be concluded that MSME1 and MSME2 are worth running because they can provide long-term benefits. Therefore, investment in dairy farming in Boyolali Regency can be recommended as a promising business opportunity